2010
DOI: 10.1155/2010/257568
|View full text |Cite
|
Sign up to set email alerts
|

Variable Viscosity on Magnetohydrodynamic Fluid Flow and Heat Transfer over an Unsteady Stretching Surface with Hall Effect

Abstract: The problem of magnetohydrodynamic flow and heat transfer of a viscous, incompressible, and electrically conducting fluid past a semi-infinite unsteady stretching sheet is analyzed numerically. The problem was studied under the effects of Hall currents, variable viscosity, and variable thermal diffusivity. Using a similarity transformation, the governing fundamental equations are approximated by a system of nonlinear ordinary differential equations. The resultant system of ordinary differential equations is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 20 publications
(4 reference statements)
0
26
0
Order By: Relevance
“…To study the effect of viscosity which varies with temperature and viscous dissipation, Pal and Mondal [16] adopted a problem of mixed convective heat transfer over a stretching surface under the influence of non-uniform heat source/sink. In a similar study Shateyi and Motsa [17] used successive linearization method to solve a set of non-linear ordinary differential equation arises in formulation of unsteady heat transfer over a stretching sheet with Hall Effect. Taking into account the variable viscosity and thermal conductivity Mahanti and Gaur [18] put forwarded some interesting results on free convective flow and heat transfer due to heat sink along an isothermal vertical plate.…”
Section: Introductionmentioning
confidence: 99%
“…To study the effect of viscosity which varies with temperature and viscous dissipation, Pal and Mondal [16] adopted a problem of mixed convective heat transfer over a stretching surface under the influence of non-uniform heat source/sink. In a similar study Shateyi and Motsa [17] used successive linearization method to solve a set of non-linear ordinary differential equation arises in formulation of unsteady heat transfer over a stretching sheet with Hall Effect. Taking into account the variable viscosity and thermal conductivity Mahanti and Gaur [18] put forwarded some interesting results on free convective flow and heat transfer due to heat sink along an isothermal vertical plate.…”
Section: Introductionmentioning
confidence: 99%
“…These methods include the Adomian decomposition method [15][16][17], differential transform method [18], variational iteration method [19], homotopy analysis method (HAM) [20][21][22][23], and the spectral-homotopy analysis (SHAM) (see Motsa et al [24,25]) which sought to remove some of the perceived limitations of the HAM. More recently, successive linearization method [26][27][28], has been used successfully to solve nonlinear equations that govern the flow of fluids in bounded domains.…”
Section: Introductionmentioning
confidence: 99%
“…The system of equations (12)- (14) together with the boundary conditions (15) were solved using a successive linearisation method (SLM) (see [22,32]). The SLM is based on the assumption that the unknown functions f (η), θ(η) and φ(η) can be expanded as…”
Section: Methods Of Solutionmentioning
confidence: 99%
“…The wall temperature, solute concentration and stretching velocity are assumed to be exponentially increasing functions. The successive linearisation method (SLM) which has been used in a limited number of studies (see [3,5,[20][21][22]32]) is used to solve the governing coupled non-linear system of equations. Recent studies such as [4,22,23] have suggested that the successive linearisation method is accurate and converges rapidly to the numerical results when compared to other semi-analytical methods such as the Adomian decomposition method, the variational iteration method and the homotopy perturbation method.…”
Section: Introductionmentioning
confidence: 99%